Necesidad de reformar el art. 101 del código del trabajo en relación con la exoneración del pago de utilidades respecto de sus operarios - Villamagua Barrigas, Manuel Jacinto (2015)
Although it is certain the work it is one of the main activities that the man carries out, since this activity is as old as the same humanity, for that reason we say that from the time that we look for work, we are already carrying out a work. The work has been object of diverse studies, considered as the physical effort or intellectual that it applies the worker; it is said that all man, for law characteristic of the nature, he/she must work to obtain the subsistence; and although the machine works finally of the intellectual work of who conceives it, it alleviates in good part but it won't be been able to eliminate completely. Conception is it considers it to him like the human being's essential manifestation and constituent that at the same time is a social rateable fact, manifested as much as ability and as duty, being an indispensable condition for the development of the mankind; with the aparecimiento of the Republic you begins to guarantee the rights of people and like they are indispensable the rights of the workers and constant so much employers in the Constitution, like in the Code of the Work. The present investigation has been carried out on a topic of social interest by such a reason and aware of the abuses and outrages made on the part of some of the qualified employers as artisans, it was traced as primordial objective to carry out the investigation to modulate whose thematic it is: "NECESSITY TO REFORM ART. 101 OF THE CODE OF THE WORK In connection with THE DISCHARGE OF THE PAYMENT OF UTILITIES CONCERNING OF THEIR OPERATIVES", the one that has been developed in all the aspects required for their definitive approval. Being able to check the vulnerability or rather the privation of certain rights of the operatives, so absurd thing because contradiction exists between the Code of the Work and the Great Letter, since this he/she says that we all are entitled the same without some exception; hence we have outlined a reformation to Arts. 101 of the Labor Code.